ASSESSMENT OF CARBON FOOTPRINT AND THERMAL COMFORT IN WELDING AND CONCRETE LABORATORY - Norain Ali; Mazlin Wellington; Zulhan Matlin (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Global warming is the phenomenon of global temperature increase from year to year due to the greenhouse effect. Currently, carbon dioxide concentrations are estimated to be most dominant in the atmosphere. Therefore, this carbon footprint study will be conducted in the institutional area to determine the actual amount of CO2 present in Politeknik Kuching Sarawak institution. Research on ways to reduce carbon dioxide emissions will also be conducted indirectly. The objective of the study was to analyze carbon dioxide footprints in skill institutions that emit large amounts of gas emissions. Adaptive thermal comfort model is methods can be identified from previous readings to record or analyze data by using Air Quality Detector, Lux Meter and Anemometer. While to refer and compare the data obtained, we refer to the existing standards that are ASHRAE 55 standards and CIBSE Guide A. The result found is carbon footprint in concrete and welding laboratory in Politeknik Kuching Sarawak institution is still in the safe range but measures or proposals to reduce carbon emissions need to be initiated to maintain safety in terms of ventilation and environment in the institution.